Electrical transport and magnetic properties of MgB2 reacted with Si and C - Chen, Soo Kien; Tan, Kwee Yong; Shaari, Abdul Halim; Xu, Xun; De Silva, S.; Yeoh, Wai Kong; Dou, Shi Xue; Kursumovic, Ahmed; MacManus-Driscoll, Judith L. (2013)
SiC is among the promising dopants which can be used to increase the critical current density of MgB2 superconductor up to the level required for producing high magnetic field. In this work, we are motivated to study how Si and C influence the electromagnetic properties of bulk MgB2 prepared by reacting the material with SiC or combination of Si and C elements (Si+C). While there is no significant change in the e-axis lattice parameter, the a-axis is smaller compared with that of the pure sample indicating substitution of C on the B site. The C substitution level was estimated based on the relative change of c with respect to a (c1a). By varying the sintering temperature, the C substitution level is different between the samples reacted with SiC and {Si+C) despite their superconducting transition temperature is close to each other. The upper critical fields were determined from the temperature and magnetic field dependence of resistive transition. These results together with the inductive critical current density were correlated to the resistivity properties and C substitution.